New Golf Course, Maraval - (:unkn) unknown (My University, 2009)
Shows men on the new golf course in Moka, Maraval.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Postcards; Trinidad and Tobago; Golfers--Trinidad and Tobago; Sports--Trinidad and Tobago; Golf courses--Trinidad and Tobago; Ball games--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Architecture--Trinidad and Tobago; Buildings--Trinidad and Tobago; Men--Trinidad and Tobago; Leisure--Trinidad and Tobago; Recreation--Trinidad and Tobago; Outdoor recreation--Trinidad and Tobago; Sports facilities--Trinidad and Tobago